The Analysis of Hospitality Department Students’ Speaking Skill in Presenting Procedural Text - Wanda Rahmadhanti; Edi Trisno (Journal of English Language Teaching, 2022)
This study was conducted to see how the fluency and accuracy of students in speaking English using text procedures on students of SMKN 9 Padang in the hospitality department of class 2. This study used descriptive research. Participants in this study were 34 students in the hospitality department. In this study, the instrument used was a speaking test for students. From the results of this study, it can be concluded that from as many as 34 students, none of the students got an E or <40. There are as many as 5 students who get an A or > 80. The average fluency and accuracy of students in speaking using procedure texts in class XI hospitality students at this school get a B value or get a score between 66-79 in speaking using procedure texts.